2014
DOI: 10.1590/0102-33062014abb3239
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition and structure of an upper montane cloud forest in the Serra da Mantiqueira Mountain Range of Brazil

Abstract: We analyzed the community structure of an upper montane cloud forest (elevation, 1900 m) in the Serra da Mantiqueira Mountain Range, in the state of Minas Gerais, Brazil. Our objective was to determine the comparative tree species richness and floristic diversity within this forest, which is at one of the higher elevations in the range, in relation to surrounding forests that are at lower elevations, adjusting for elevational gradients. Within 15 permanent plots (40 × 10 m each), we tagged all tree individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
(30 reference statements)
0
14
0
2
Order By: Relevance
“…Conversely, the Atlantic cloud forests were shown to be floristically distinct from the equally wet coastal Atlantic rain forests, with Drimys brasiliensis, Ilex microdonta, and Weinmannia paulliniifolia being key indicator species for the cloud forest (Bertoncello et al, 2011). In the SdM, cloud forests are also the preferred habitat of species like Cabralea canjerana, Lamanonia ternata, Myrcia splendens, Myrsine umbellata, as well as Prunus myrtifolia (Pompeu et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the Atlantic cloud forests were shown to be floristically distinct from the equally wet coastal Atlantic rain forests, with Drimys brasiliensis, Ilex microdonta, and Weinmannia paulliniifolia being key indicator species for the cloud forest (Bertoncello et al, 2011). In the SdM, cloud forests are also the preferred habitat of species like Cabralea canjerana, Lamanonia ternata, Myrcia splendens, Myrsine umbellata, as well as Prunus myrtifolia (Pompeu et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…comprises a number of sub-types, including various rain forests and semi-deciduous forests as well as subtropical Araucaria forest whose floristics in southeastern Brazil has been described in some detail by Oliveira-Filho and Fontes (2000). Atlantic cloud forests have been much less researched botanically (Falkenberg & Voltolini, 1995;Pompeu et al, 2014) but a recent regional study indicated they constitute a distinct floristic and phytogeographical unit (Bertoncello et al, 2011). This opens up possibilities for mapping regional and local cloud forest extent based on the demonstrated occurrence of forest formation A C C E P T E D M A N U S C R I P T units (Webster, 1995).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. (2018), Oliveira-Filho et al (2013), and Pompeu et al (2014), among others. Nevertheless, the great environmental heterogeneity presented by this mountain chain has not been sufficiently detailed (Martinelli 2007).…”
Section: Introductionmentioning
confidence: 96%
“…The ten sampling units were compared in relation to species abundance in each unit using correspondence analysis (CA). Species lists of UMF from six other localities in Paraná, Minas Gerais and São Paulo states (Portes et al 2001, França & Stehmann 2004, Meireles et al 2008, Valente et al 2011, Pompeu et al 2014, Meireles & Shepherd 2015 ; Table 1) were used in non-metric multidimensional scaling (NMDS) using the Bray-Curtis dissimilarity index to obtain the floristic similarity between locations. In NMDS, we considered only the woody component, including tree ferns.…”
mentioning
confidence: 99%